Molecular probing of low-temperature incommensurate phases: Biological Systems at Low Temperatures - Kikas, J.; Suisalu, A.; Laisaar, A.; Kuznetsov, An. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Two-dimensional (2D) excitation-emission spectra of biphenyl doped with free-base chlorin were measured at 5 K under various pressures up to 350 MPa. Besides the features related to zero-phonon lines and their phonon sidebands, a broad spectral band amounting to 80% of the total intensity at 5 K was revealed in the 2D spectra. The obtained inhomogeneous distribution function shows drastic changes with increasing pressure — the triplet structure observable at normal pressure in the incommensurate phase ICIII of biphenyl converges to a singlet in the high-pressure commensurate phase CI. These observations are assumed to reflect specific for incommensurate phases relaxation after an optical excitation of probe molecules and interaction of them with the incommensurate modulation wave.